2016
DOI: 10.1111/jon.12379
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial Doppler as a Predictor of Ischemic Events in Carotid Artery Dissection

Abstract: TCD can identify a subgroup of patients with CCADW who are at high risk of IE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 24 publications
1
20
0
2
Order By: Relevance
“…This imaging protocol includes MRA and multicontrast MRI sequences that suppress the signal from adjacent tissue and blood to highlight VW pathologies of both intracranial and extracranial vessels (Figs. [1][2][3][4][5]. 9 This can provide a wealth of new information that timeof-flight (TOF) MRI sequences and other luminal imaging techniques cannot deliver.…”
Section: Vessel Wall Mrimentioning
confidence: 99%
See 2 more Smart Citations
“…This imaging protocol includes MRA and multicontrast MRI sequences that suppress the signal from adjacent tissue and blood to highlight VW pathologies of both intracranial and extracranial vessels (Figs. [1][2][3][4][5]. 9 This can provide a wealth of new information that timeof-flight (TOF) MRI sequences and other luminal imaging techniques cannot deliver.…”
Section: Vessel Wall Mrimentioning
confidence: 99%
“…4 Transcranial Doppler ultrasonography has also been used in the diagnosis of acute ischemic strokes in the setting of spontaneous cervical arterial dissections. Brunser et al 5 found that the presence of an MES and abnormal vasomotor reactivity, as determined by an abnormal breath hold index, was significantly predictive of a future ischemic event in these patients.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Of patients with symptomatic carotid disease, two had arterial dissection at the time of monitoring by TCD, and in one of these, MES were found. Some other studies have demonstrated the importance of microembolism in TCD monitoring as a risk factor for stroke in carotid dissection [30][31][32]. One of the patients examined in the present study was diagnosed with pulmonary thromboembolism and left-toright shunts could be detected with a simple bubble test, without contrast.…”
Section: Discussionmentioning
confidence: 51%
“…144 MES have been also detected in individuals with cervical artery dissections and have been associated with the incidence of cerebrovascular events. 145 Aortic dissections, in particular Stanford type A, may be complicated with ischemic stroke. 146 There are currently no published reports of MES in patients with aortic dissection.…”
Section: Aortic Arch Atheroma and Ascending Aortic Dissectionmentioning
confidence: 99%